Learning from Home Satisfaction for Graduate Biology Students in the COVID-19 Era - Niyonsaba, Theophile; Paidi, Paidi (Universitas Negeri Semarang, 2021)
The study aims to assess the level of satisfaction for Biology master’s students understudying in online learning mode henceforth learning from home at Yogyakarta State University. A structured questionnaire was employed to view student satisfaction around 7 dimensions namely; resource availability and well-operating tools, instructor support interaction, lesson quality and quality of delivery, assessment mechanism, teaching method, learning environment, and satisfaction. Of 49 students was surveyed and asked to answer questions relating to learning from home experience and the level of their satisfaction. Out of which participants over 80% were females and around 19% males where the major part of them belonged to 21-30 years of age. Data were analyzed using SPSS software and item’s reliability was found higher (over 0.75) that substantiated the reliability of the questionnaire used. Based on calculating the mean and SD, data reveal that students are highly satisfied by the learning from home system. Findings suggest that the implementation of the learning from home program was a very great idea during this dire disease era as the majority of the students supported the initiative. However, the study discovered also that the quality and distribution of internet connectivity, non-updated devices for some students was the main challenge that might be rending online learning more ineffective.